Capacity Building pada POKDARWIS Manggar dalam Pengembangan Desa Wisata Wonolopo Kecamatan Mijen Kota Semarang - Dyah Hutami, Aprilia; Hanani, Retna; Zarkasyi Rahman, Amni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The Tourism Awareness Group (POKDARWIS) is the driving force of tourism at the village level. POKDARWIS Manggar is the manager of Wonolopo Tourism Village, Mijen District, Semarang City. POKDARWIS Manggar as the manager of the Tourism Village has several problems such as the lack of human resources, the lack of participation for the surrounding community, and the uneven knowledge of tourism villages among POKDARWIS members. The purpose of this research is to find out the capacity development of POKDARWIS Manggar in the development of Wonolopo Tourism Village along with the driving and inhibiting factors. This research method is descriptive qualitative. The data collection techniques used were interviews, observation, documentation, and literature study. Capacity development was studied using the theory proposed by Grindle which includes three dimensions of capacity development, namely human resource development, organizational strengthening, and institutional reform. The results showed that POKDARWIS Manggar has conducted capacity development in its organization, but experienced several obstacles in its implementation. The driving factors are shared commitment, leadership, innovation, internal participation, networks, and information. The inhibiting factors for capacity building at POKDARWIS Manggar are regulation and community participation.